2015
DOI: 10.4236/aasoci.2015.51001
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Study on the Profile of Human Smugglers in Turkey

Abstract: Illegal migration is an impalpable phenomenon with complicated dimensions. Thousands of people leave their homelands every year due to a number of reasons such as civil wars, terrorism, economic difficulties, and social oppressions. With their flexible modus operandi, migrant smugglers benefit from individuals or groups that wish to immigrate for a more comfortable life. In order to reach a complete perception of illegal migration one needs to draw an accurate profile of migrant smugglers. At this end, data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…On the assumption of this, the most confidential informants are men. The fact that crime at the border has a "male face" is confirmed by the results of the studies (Içli, Sever, & Sever, 2015;Zhang & Chin, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…On the assumption of this, the most confidential informants are men. The fact that crime at the border has a "male face" is confirmed by the results of the studies (Içli, Sever, & Sever, 2015;Zhang & Chin, 2002).…”
Section: Discussionmentioning
confidence: 71%
“…The majority of ivory [ 44 , 59 ], pangolin [ 2 ] and rhino horn [ 40 ] trade originates outside of China, therefore smugglers require better management, organization, internet and/ or computer skills (associated with higher education) than do agricultural hunters [ 60 ]. These skills enable offenders with higher schooling to negotiate illicit international trade deals, while attempting to evade detection [ 61 , 62 ]. For example, 11 offenders (9 men, 2 women), comprising a network illegally trafficking a tiger pelt, 1.35 kg of rhino horn and 32.55 kg of ivory from Vietnam, were sentenced to 8 years in jail in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of studies and articles have shown how violence and abuse are recurring features of the migrant-smuggler relationship, especially when it comes to collecting money and enforcing contracts (e.g. I. çli, Sever, and Sever 2015; UNODC 2010).…”
Section: The Call: Becoming a Smugglermentioning
confidence: 99%
“…See, among others, Achilli (2017); Antonopoulos and Winterdyk (2006); Baird (2016); I. çduygu (2007); İçduygu and Toktas (2002); İduygu and Yükseker (2012); İli, Sever, and Sever (2015); Mandić (2017); Papadopoulou (2004); and Triandafyllidou and Maroukis (2012).…”
mentioning
confidence: 99%